Estudo do potencial de aditivo cristalizante como estimulador de autocicatrização de fissuras de matrizes cimentícias - Oliveira , Aline de Souza (2019)
In this thesis, cement slurries were designed with low healing potential in order to evaluate crystalline admixture (CA) behavior. CA that is claimed to provide (stimulated) autogenous healing. Consequently. these inclusions in cementitious materials aimed to improve the self-healing characteristics for the structure. Zonal isolation and mechanical support are some desirable properties that can be enhanced in the cement sheath of the oil wells in pre-salt areas. Therefore, the healing recovery of cement slurries was evaluated according to different CA dosages (0.5%, 1%, and 2% by cement weight), and two crack width classes under loading (0.1 mm and 0.2 mm). The effectiveness of the healing process was verified by the mechanical regain and durability enhance. The addition of polypropylene fibers (PP) in the pastes enabled the induction of a single controlled crack width by the splitting tensile test. The macrostructural results were related to microstructural analysis. Hydrates localized in the microstructure cement matrix and crack width were identified and quantified. Kinetic hydration reactions were measured as well. These techniques aimed to contribute to the understanding of physical-chemical mechanisms promoted by the CA. The specimens were submitted to splitting tensile and gas permeability tests. Self-healing quantification was based in recovery indexes, such as Load Recovery Index, Damage Recovery Index and Crack Sealing Index. The results confirmed recovery in the evaluated properties after the healing process for both crack widths studied. The best performance was achieved with 2% wt., especially, when CA was used combined with polypropylene fibers.